FENOMENA HOAX: Tantangan terhadap Idealisme Media & Etika Bermedia - Fabianus Fensi (Universitas Bunda Mulia, 2018)
ABSTRACTThe hoax phenomenon is a historical reality. He was born along with the birth of the era of information media freedom. Hoaxes are often damaging to a pluralistic society. History records that hoaxes destabilize harmony of a society. Therefore the hoax must be terminated immediately. This paper uses a textual literature study approach. Hoax phenomenon is placed in the tension between media idealism and media ethics. The scope of the discussion began with a review of some of the country's formal regulations, such as the Law that had been produced. For the author, state regulation of media life is an ideal condition (media idealism) where the state is based on its capacity to regulate what must be broadcast. The result is that ideal conditions do not always have an impact in reality. Many rules are violated in the practice of media, especially social media. So, there should be room to be filled in to overcome this gap, namely an ethical commitment as a normative necessity for social media activists. Law enforcement alone is not enough so it must also be equipped with other social capital, namely: the firmness of citizens' attitudes, are social media users to maintain the integrity of society. The integrity is possible by the determination of the social media community to ensure a truth of the message before it is broadcast to the public; Maintain the privileges inherent in each individual; Strictly separating the realm of private issues from public problems; Reveal a message that avoids lying, slander, and attacking others' personal motives; and full awareness that the cultural diversity of society is sensitive. All of these are referred to as ethical principles that must be considered as guidelines for living together as a nation.Keywords: Ethics, Hoaxes, Social Media, Plurality, Regulation.ABSTRAKFenomena hoax adalah sebuah kenyataan sejarah. Dia lahir bersamaan dengan kelahiran era kebebasan media informasi. Namun, keberadaannya seringkali merusak tatanan masyarakat yang plural. Sejarah mencatat bahwa hoax menggoyahkan kerukunan, bahkan perpecahan masyarakat. Karena itu hoax harus segera diakhiri. Tulisan ini menggunakan pendekatan kajian literatur tekstual, dimana fenomena hoax ditempatkan dalam ketegangan antara idealisme media dan etika bermedia. Cakupan pembahasan dimulai dari tinjauan terhadap beberapa regulasi formal negara, seperti Undang-undang yang pernah dihasilkan. Bagi penulis, regulasi negara atas kehidupan media adalah kondisi ideal (idealisme media) dimana negara berdasarkan kapasitasnya mengatur apa yang harus disiarkan. Hasilnya bahwa kondisi ideal tidak selalu berdampak dalam kenyataannya. Banyak aturan dilanggar dalam praktik bermedia, terutama media sosial. Maka, seharusnya ada ruang yang harus diisi untuk mengatasi kesenjangan tersebut, yaitu sebuah komitmen etis sebagai keharusan normatif bagi para pegiat media sosial. Penegakan hukum saja tidak cukup maka harus pula dilengkapi modal sosial yang lain, yaitu: keteguhan sikap warga negara, pengguna media sosial untuk menjaga keutuhan masyarakat. Keutuhan itu dimungkinan oleh keteguhan masyarakat media sosial untuk memastikan sebuah kebenaran pesan sebelum disiarkan kepada publik; Menjaga hak istimewa yang melekat pada setiap individu; Memisahkan dengan tegas ranah persoalan privat dari persoalan publik; Mengungkapkan pesan yang menghindari motif-motif bohong, fitnah, dan menyerang pribadi orang lain; dan kesadaran penuh bahwa keragaman budaya masyarakat adalah sensitif. Semua ini disebut sebagai prinsip etis yang harus dianggap sebagai pedoman hidup bersama sebagai bangsa.Kata Kunci: Etika, Hoax, Media Sosial, Pluralitas, Regulasi.